QARAQALPAQSTAN SHARAYATÍNDA SHÍǴÍS KATRANÍ (CRAMBE ORIENTALIS L.)NÍŃ BIO-EKOLOGIYALÍQ ÓZGESHELIKLERI - Baltabaev, M.T.; Ismamutova, A.T. (SCIENCE and SOCIETY, 2024)
In the article, the bio-ecological specificity of the eastern katra (crambe orientalis l.) in the conditions of Karakalpakstan is studied in the cultural conditions.